ACCESS TO SINGLE PILL COMBINATIONS IN NATIONAL HYPERTENSIVE CONTROL PROGRAMS: IS PRICING A BARRIER?. (April 2021) - Negi, Sagri; Sahoo, Swagata Kumar; Mahajan, Tanushree; Swaroop, Kishan; Neupane, Dinesh; Moran, Andrew; Sharma, Bhawna; Pathni, Anupam Khungar
Abstract : Objective: Most patients with hypertension require two or more medicines to control their blood pressure. Single pill combination (SPC) antihypertensive medicines facilitate simpler dosing schedules, decrease pill burden, increase patient medication adherence, simplify procurement and distribution. This study uses a private sector pharmaceuticals database to explore whether prices are a barrier to access SPCs in hypertension control programmes. Design and method: Trends in sales of anti-hypertensive medications in India were analysed in private sector pharmaceutical sales dataset from IQVIA Consulting. Price information was collated for medicines that attributed to 70% of sales in terms of number of tablets sold. Maximum Retail Prices of 11 SPCs and their associated Fixed Dose Equivalents (FDEs; same medications and doses as separate pills) were gathered through a publicly available website called "1mg" between November 2019-January 2020. Results: In India, the market share of 2-drug-SPCs and 3-or-more-drug SPCs increased from 2016–2018 at a compounded annual growth rate of 5.5% and 16.1% respectively. In 2018, 2-drug-SPCs (36.3%) had the highest market share in terms of quantity of medicines followed by FDE of SPC components, such as calcium channel blockers (18.3%), beta blockers (16.3%), angiotensin receptor blockers (14.6%), diuretics (5.3%), and ACE-Inhibitors (3.6%). Share of 3-or-more-drug SPCs (2.0%) was very small. While nine of 11 SPCs had an average price higher than sum of the average price of their component FDEs (Range 2.6% - 45.9% higher), a comparison of SPCs and FDEs by the same manufacturer showed that for eight 2-drug-SPCs there was at least one company for each molecule whose SPC was priced lower than the sum of the price of FDEs (Range -71.47% -124.73%). Conclusions: SPCs are increasingly preferred for hypertension treatment in the Indian private sector. The World Health Organization recently included four SPCs for hypertension management in its Essential Medicine List. India has a vibrant and competitive hypertensive medicines market. Examples discovered in this dataset of minimal-to-no price difference suggest that price need not be a barrier to accessing SPCs, and that market forces can further drive down prices with substantial advantages for patients and hypertension control programmes.